PERTUMBUHAN DAN HASIL BAWANG DAUN (Allium fistusolum) TERHADAP PEMBERIAN PUPUK KANDANG AYAM DAN ZAT PENGATUR TUMBUH PADA TANAH GAMBUT PEDALAMAN: APPLICATION OF CHICKEN MANURE FERTILIZER AND PLANT GROWTH REGULATORS FOR INCREASING THE GROWTH AND YIELD OF LEAF ONION (Allium fistusolum) ON PEAT LAND - Abdul Hamid, Syahrudin; Darung, Untung; Taufik Norhidayat, Muhammad; Kresnatita, Susi; Syahid, Abdul; Vetrani Asie, Kambang (AgriPeat, 2025)
The purpose of this experiment were to find out the interaction growth and yield of leaf onion (Allium fistusolum) on the giving of chicken manure fertilizer and plant growth regulator on peat land. Tihs study used Completely Randomized design (CRD) of factorial pattern with two factors. The first factor was applying of chicken manure fertilizer (K) consisting of 4 (four) levels, namely : : K0 = 0 ton.ha-1, K1 = 5 ton.ha-1, K2 = 10 ton.ha-1 and 15 t ha-1. The second factor was the provision of concentration growth regulators (Z) which consists of 4 (four) levels, namely : Z0 = 0 ml L-1 water, Z1 = 1 ml L-1 water, Z2 = 3 ml L-1 water and Z3 = 5 ml L-1 water. . The results showed the interaction of chicken manure and growth regulators affected the number of leaves, fresh weight of plants and dry weight of plants. The combination of 10 t ha-1 chicken manure and 5 ml L-1 water growth regulator treatment was able to increase the yield of spring onions with a fresh weight of 32.67 g plant-1.